Compactness Effect on Bending Behavior of Cold Formed Steel Beams - Yaman, Zeynep; Ağcakoca, Elif (Periodica Polytechnica Civil Engineering, 2020)
With respect to the determination of the strength of the structural steel members, first the behavior of cross section and then that of the overall member should be considered. In this study, it is aimed to determine the compactness behavior of U-shaped steel sections that exposed to minor-axis bending. Thus, the study questions whether the U-shaped cross section exhibits sufficient dimensions for the collapse mechanism to occur by aiding the moment redistribution in the structural system by supplying sufficient hinge rotation capacity. In order to investigate compactness behavior, three different channel section steel profiles are selected. Four point experimental tests are carried out to validate finite element models of the selected profiles. Upon validated finite element models, parametric studies are performed with finite element analyses. In the parametric study two steel classes, different beam lengths and cross-sectional geometries are taken as parameters. At the end of the study the plate slenderness condition required for plastic design calculated based on Eurocode3 is evaluated with the results of parametric study.